Cryopreservation of dendritic cells for cancer therapy - Deeb, Tarek; Zeh, Lena; Rittinghaus, Tim; Dettmer-Richardt, Claudia; Grammel , Simon; Glasmacher , Birgit (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):300